2022
DOI: 10.1002/hed.27180
|View full text |Cite
|
Sign up to set email alerts
|

Delayed tracheal rupture following transoral endoscopic thyroidectomy vestibular approach: Case report and review of the literature

Abstract: Background Although the transoral endoscopic thyroidectomy vestibular approach (TOETVA) has been proven to be a safe procedure for select patients, as it is a novel approach, all associated complications require adequate attention. Methods We presented a 49‐year old woman who underwent TOETVA developed delayed tracheal rupture 1 week after surgery. An extensive search of literature was carried out using PubMed, Embase, and Web of Science for studies reporting tracheal injury following endoscopic thyroidectomy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Weng et al reviewed the literature and found ten articles on tracheal injury following endoscopic thyroidectomy. In those cases, both intraoperative and delayed tracheal injury were reported [ 30 ]. Intraoperative tracheal perforation was caused especially by the Veress needle and accidental dissection, whereas thermal injury was more likely to cause delayed rupture resulting in tracheal necrosis [ 22 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Weng et al reviewed the literature and found ten articles on tracheal injury following endoscopic thyroidectomy. In those cases, both intraoperative and delayed tracheal injury were reported [ 30 ]. Intraoperative tracheal perforation was caused especially by the Veress needle and accidental dissection, whereas thermal injury was more likely to cause delayed rupture resulting in tracheal necrosis [ 22 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regression analysis of TOETVA complications by Fernandez-Ranvier G et al showed the most significant reduction in complications in case 12, with the risk and severity of complications decreasing significantly as the number of cases increased ( 23 ). In addition, delayed tracheal rupture was reported after 1 week of TOETVA treatment ( 43 ). Previous studies have shown judicious use of energy instruments and a safe distance from the windpipe can avoid tracheal damage..…”
Section: Discussionmentioning
confidence: 99%